A qualitative study exploring how students' conceptualisations of lifelong learning develop in an undergraduate medical training programme. Issue 3 (2nd September 2022) - McMillan, James C. D; Jones, Linda
ABSTRACT: There is currently a paucity of evidence regarding how medical undergraduate training influences students' attitudes and skills for lifelong learning (LL). This study describes medical graduates' conceptualisations of LL at the University of Dundee and proposes a provisional theory regarding related curriculum influences. Using a methodology informed by scientific realism, semi-structured interviews were employed to explore six graduating medical students' conceptualisations of and preparedness for LL. Findings were thematically analysed and aligned with existing educational theories. Graduates characterised LL as a continual process which emphases reflection, responsibility for learning, and maintaining motivation. Their conceptualisations did not translate readily beyond professional medical practice. The strongest curriculum influences were experiences in the authentic clinical environment, use of learning portfolios, and the intercalation of a medical science degree. In the absence of formal teaching, medical students' conceptualisations of LL develop in accordance with both the implicit prevailing professional narrative and from curriculum interventions which: increase their sense of relatedness with their community of practice; provide autonomy in learning; and engender a sense of responsibility to learn. This provisional theory could be valuable in guiding the teaching and assessment of LL in-line with contemporary graduate outcome frameworks.